ANALISIS RISIKO CEMARAN MIKROBIOLOGIS PADA PENGELOLAAN PERALATAN MAKAN DAN MINUM DI KANTIN SEKOLAH DASAR - Christiva, Regina Haris; Rusmiati, Rusmiati; Setiawan, Setiawan (Poltekkes Kemenkes Tanjung Karang, 2020)
Food services must pay attention to a proper sanitary and hygiene practices, including on the eating and drinking utensils used in school cafetaria. Eating and drinking utensils management must prevent contamination, so it does not pose any risks of adverse health effect to the students. Preliminary test showed that the glass swab sample total plate count result was 2.894,6 CFU/cm2, thus it did not comply to the health regulation. This research aims to analyze the risks of managing eating and drinking utensils in the school cafetaria using the HACCP method by determining its critical control points (CCPs).This is an observasional study in which the object was two state elementary school cafetaria in Pakis Village, Sawahan region, Surabaya. Data was collected through observations, interviews, and samplings. Total plate count was measured on the utensils Â swab samples, while E.coli and total coliform was counted on the washing water samples.Based on the HACCP approach, the equipment management flow starts with handwashing, followed by using, washing and storing utensils. As from the result suggested, it is known that there are microbiological hazards in the utensils management, causes of risks originated from the utensils management, there are necessary control measures, CCPs are identified in the utensils management flow, and equipment management is able to pose risks of contamination and disease transmission. Causes of risks from the utensils management include washing water microbiological quality and inadequate washing stage. The necessary control measures can be applied to the identified CCPs, namely at the scraping, washing, rinsing, sanitizing, and drying stages.